Kontinuitas Gorga Batak Toba - Sofi Andriyanti (Pascasarjana ISBI Bandung, 2019)
This article is wri!en based on the result of research entitled “Gorga Batak Toba di Kabupaten Samosir: kontinuitas dan perubahan bentuk dan fungsi”, conducted in 2014 - 2015. The focus of this writing is on three main issues: the form and function of traditional gorga in Batak Toba houses before 1970s; the development of form and function of ‘new’gorga in the modern buildings that have been developed since 1970s to the present; and why there is continuity and changes on form and function of gorga. A qualitative method in narrative-descriptive with historical approachis used to fi nd out the continuity of gorga Batak Toba in Batak Toba society, and internal and external factors are analyzed to see the causes of the continuity. The data are collected through literature study, observation, and interview with researchers role as the key instrument. The result shows that the survival of gorga in Batak Toba society can be described simply, that is, from existing to nothing, and from nothing to rise again into being, but in the ‘new’ form.Keywords: gorga, continuity, Batak Toba people